REFUSAL STRATEGIES USED BY JAVANESE IN NOVEL PINATRI ING TELENG ATI BY TIWIEK AS - Widya widya; Erika Agustiana (Pujangga: Jurnal Bahasa dan Sastra, 2023)
This research was a qualitative research that aimed at examining the refusal strategies and refusal seqences used by Javanesse in the novel Pinatri Ing Teleng Ati karya Tiwiek AS. The research was done in three steps, that is, collecting data, analyzing data, and presenting the results. Language variation used in this analysis is Javanese vernacular language which used in daily conversation. The results showed that all three refusal strategies, direct, indirect, and adjunct, were used by characters in the novel. Direct strategies consisted of performative statement while indirect strategies consisted of reason/explanation, statement of alternative, statement of principle, statement of phylosophy, attempt to dissuade interlocutor, acceptance functions as refusal, and avoidance. Adjunct strategies consisted of pause filler and gratitude. Furthermore, the characters also used three sections of refusal strategy, pre-refusal, lead act, and post-refusal. The results also revealed that not only social factors influencing the refusal strategies used but also the state of relationship between interlocutors. The deteriorating relationships will increase the tendency of choosing the higher level face-threatening strategies.